2016
DOI: 10.1007/s00170-016-8904-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of injection molding process parameters for short cycle time and warpage reduction using conformal cooling channel

Abstract: In this paper, cooling performance of conformal cooling channel in plastic injection molding (PIM) is numerically and experimentally examined. To examine the cooling performance, cycle time and warpage are considered. Melt temperature, injection time, packing pressure, packing time, cooling time, and cooling temperature are taken as the design variables. A multi-objective optimization of the process parameters is then performed. First, the process parameters of conformal cooling channel are optimized. Numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 34 publications
1
48
0
2
Order By: Relevance
“…The effect of para-conformal cooling on the temperature development of the IM inserts is shown in Figure 3 (step 2a) and Figure 4 (step 2b) whereas the para-conformal cooling approach will allow for a shorter cooling time as the cooling temperature is already lower at the time of ejection. This conforms with research like [6] where the authors claim to reach an improvement of cycle time due to conformal cooling by 53 %. The development steps 3a and 3b elaborate on the fact that fiber-reinforced PhP IM inserts provide a longer lifetime.…”
Section: Resultssupporting
confidence: 91%
“…The effect of para-conformal cooling on the temperature development of the IM inserts is shown in Figure 3 (step 2a) and Figure 4 (step 2b) whereas the para-conformal cooling approach will allow for a shorter cooling time as the cooling temperature is already lower at the time of ejection. This conforms with research like [6] where the authors claim to reach an improvement of cycle time due to conformal cooling by 53 %. The development steps 3a and 3b elaborate on the fact that fiber-reinforced PhP IM inserts provide a longer lifetime.…”
Section: Resultssupporting
confidence: 91%
“…Warpage and cycle time [128,129] Shrinkage and clamping force [130] Warpage [131] function to the resulting sum in order to determine the output. e ANN learns to approximate the functions through a training process and adjusts their weights and biases until a performance index reaches a preset threshold value.…”
Section: Taguchi Methodmentioning
confidence: 99%
“…e ANN learns to approximate the functions through a training process and adjusts their weights and biases until a performance index reaches a preset threshold value. Kitayama et al [128,129] developed an injection mold with a conformal cooling channel, combined with computer simulation, using a radial basis function network for multiobjective optimization of the injection process. e cycle time improved by 26%, and the warpage improved by 14% using an optimal combination of process parameters.…”
Section: Taguchi Methodmentioning
confidence: 99%
“…The sensitivity analysis together with boundary element method presented a good performance; however, they are not applicable to real industrial parts. Kitayama et al [20] examined the cooling design of conformal channels, analyzing the cycle time and the warpage in industrial molded parts through numerical and experimental tests. The results confirmed that conformal cooling is effective due to the short cycle time and the warpage reduction.…”
Section: Background and Related Workmentioning
confidence: 99%